Immobilization of L-asparaginase on Oxidized Bacterial Cellulose to Improve the Thermal Stability of the Enzyme - Shishparenok, A.N.; Koroleva, S.A.; Zlotnikov, I.D.; Gladilina, Yu.A.; Pokrovskaya, M.V.; Alexandrova, S.S.; Zhdanov, D.D. (Biomedical Chemistry: Research and Methods, 2024)
Bacterial cellulose (BC) membranes can be modified for covalent immobilization of macromolecules. One type of modification is oxidation, after which the oxidized BC membrane (OBC) could be used as a matrix for covalent immobilization of enzymes. In this work, the BC membrane was chemically oxidized with sodium periodate (NaIO4) to increase the stability of immobilized mesophilic L-asparaginase (L-ASNase) from Erwinia carotovora (EwA). IR spectroscopy confirmed the immobilization of L-ASNase EwA on OBC membranes. Immobilization of the enzyme increased its temperature optimum for its activity by 15°C and raised the inactivation temperature to 60°C. The OBC membrane could be used as a potential carrier for covalent immobilization of enzymes to improve their pharmacological properties by increasing their thermostability.